The Complete Mitochondrial Genome of the Stalk-Eyed Bug Chauliops fallax Scott, and the Monophyly of Malcidae (Hemiptera: Heteroptera) - Li, Teng (Public Library of Science, 2013)
Chauliops fallax Scott, 1874 (Hemiptera: Heteroptera: Malcidae: Chauliopinae) is one of the most destructive insect pests of soybean and rice fields in Asia. Here we sequenced the complete mitochondrial genome of this pest. This genome is 15,739 bp long, with an A+T content of 73.7%, containing 37 typical animal mitochondrial genes and a control region. All genes were arranged in the same order as most of other Heteroptera. A remarkable strand bias was found for all nine protein coding genes (PCGs) encoded by the majority strand were positive AT-skew and negative GC-skew, whereas the reverse were found in the remaining four PCGs encoded by the minority strand and two rRNA genes. The models of secondary structures for the two rRNA genes of sequenced true bugs and Lygaeoidea were predicted. 16S rRNA consisted of six domains (domain III is absent as in other known arthropod mitochondrial genomes) and 45 helices, while three domains and 27 helices for 12S rRNA. The control region consists of five subregions: a microsatellite-like region, a tandem repeats region and other three motifs. The unusual intergenic spacer between tRNA-H and ND4 only found in the species of Lygaeoidea, not in other heteropteran species, may be the synapomorphy of this superfamily. Phylogenetic analyses were carried out based on all the 13 PCGs showed that Chauliopinae was the sister group of Malcinae and the monophyly of Lygaeoidea.